Pigment Dispersing Factor Is a Circadian Clock Output and Regulates Photoperiodic Response in the Linden Bug, Pyrrhocoris apterus - Kotwica-Rolinska, Joanna; Damulewicz, Milena; Chodakova, Lenka; Kristofova, Lucie; Dolezel, David (Frontiers in Physiology, 2022)
Daily and annually cycling conditions manifested on the Earth have forced organisms to develop time-measuring devices. Circadian clocks are responsible for adjusting physiology to the daily cycles in the environment, while the anticipation of seasonal changes is governed by the photoperiodic clock. Circadian clocks are cell-autonomous and depend on the transcriptional/translational feedback loops of the conserved clock genes. The synchronization among clock centers in the brain is achieved by the modulatory function of the clock dependent neuropeptides. In insects the most prominent clock neuropeptide is Pigment Dispersing Factor (PDF). Photoperiodic clock measures and computes the day and/or night length and adjusts physiology accordingly to the upcoming season. The exact mechanism of the photoperiodic clock is and its direct signaling molecules are unknown but, in many insects, circadian clock genes are involved in the seasonal responses. While in Drosophila, PDF signaling participates both in the circadian clock output and in diapause regulation, the weak photoperiodic response curve of D. melanogaster is a major limitation in revealing the full role of PDF in the photoperiodic clock. Here we provide the first description of PDF in the linden bug, Pyrrhocoris apterus, an organism with a robust photoperiodic response. We characterize in detail the circadian and photoperiodic phenotype of several CRISPR/Cas9-generated pdf mutants, including three null mutants and two mutants with modified PDF. Our results show that PDF acts downstream of CRY and plays a key role as a circadian clock output. Surprisingly in contrast to the diurnal activity of wild-type bugs, pdf null mutants show predominantly nocturnal activity, which is caused by the clock-independent direct response to the light/dark switch. Moreover we show that together with CRY, PDF is involved in the photoperiod-dependent diapause induction, however its lack does not disrupt the photoperiodic response completely, suggesting the presence of additional clock-regulated factors. Taken together our data provide new insight into the role of PDF in the insects circadian and photoperiodic systems.